Analisis Kesalahan Dalam Pemecahan Masalah Ditinjau dari Adversity Quotient Siswa Berdasarkan Prosedur Newman - Febry Azmiana Siregar; Asrin Lubis (Journal of Natural Sciences, 2022)
This study aims to analyze the types of errors and the factors that cause students to make mistakes in solving problems based on the Newman method with Adversity Quotient (AQ). This research is a qualitative descriptive study with the research subjects namely 5 students of class VII-B SMP Negeri 6 Medan according to their respective AQ categories. The instruments used in this study were ARP questionnaires, problem solving test questions, and interview guidelines. Based on the results of the study, students in the AQ Quitter category made mistakes in reading, understanding, modifying, processing, and writing the final answer. Students with the AQ Transition from Quitter to Camper category made errors in reading, comprehension, transformation, and processing skills. Students in the AQ Camper and Transition from Camper to Climber categories made errors in processing skills and writing final answers. AQ Climber category students made mistakes in understanding, processing, and writing the final answer. Factors that cause students to misread because students forget. The misunderstanding is because you don't understand the point of the question. Transformation errors are caused by not knowing the formula and not knowing the steps to solving the problem. Agility due to lack of precision and haste. Failed to write the final answer due to an error in the previous stage